How Heaven Works : The Collective Shamanic Journeys of Phạm Công Tắc and the Syncretic Afterworld of Caodaism - Hartney, Christopher, (Numen Book Series ;, 2024)
In 1948, Vietnam's great 20th Century mystic Phạm Công Tắc (1890-1959) began a series of sermons making Caodaism's claims to universal salvation the clearest. In only two decades, Caodaism had stamped its fast-growing presence on the nation. With potent creative and poetic skill Phạm Công Tắc invited his co-religionists to take a shamanic journey with him to examine the heavens and literally see how they would be saved. The 35 sermons translated here are provided with a commentary and extensive introduction by Hartney. How Heaven Works is a fascinating insight into the deep connection between shamanic atmosphere, literature, and Modern syncretic concepts of salvation. See Less